1963
DOI: 10.1126/science.141.3577.268
|View full text |Cite
|
Sign up to set email alerts
|

Ribonucleic Acid: Effect on Conditioned Behavior in Rats

Abstract: Acquisition of a behavioral response motivated by shock was enhanced in rats chronically treated with yeast ribonucleic acid, and resistance to extinction was greater in rats so treated than in controls. This extends the role of ribonucleic acid to include a behavioral effect in laboratory mammals treated with a purified preparation from yeast.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
14
0

Year Published

1965
1965
1971
1971

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 62 publications
(14 citation statements)
references
References 5 publications
0
14
0
Order By: Relevance
“…Again using the same Ss, the fourthe},:perimentbegan on the 56th injection day and was an attempt to replicate the study of Cook et al (1963). The results show that the animals given injections of RNA made fewer errors during acquisition of the pole-climbing response (p < .05 two-tailed test) and made more responses when shock was no longer being given (p < .05 two-tailed test).…”
Section: Methodsmentioning
confidence: 93%
See 1 more Smart Citation
“…Again using the same Ss, the fourthe},:perimentbegan on the 56th injection day and was an attempt to replicate the study of Cook et al (1963). The results show that the animals given injections of RNA made fewer errors during acquisition of the pole-climbing response (p < .05 two-tailed test) and made more responses when shock was no longer being given (p < .05 two-tailed test).…”
Section: Methodsmentioning
confidence: 93%
“…Yeast ribonucleic acid (RNA) was first mentioned as having beneficial effects on memory by co-workers (1961, 1963) who reported that RNA administered in tablet form or by intravenous injection produced clinical improvement in patients suffering from senile memory impairmenL This effect was later studied by Cook et al (1963) who showed that yeast RNA (160 mg/kg I.P.) increased the rate at which rats learn the response of climbing a pole to escape shock.…”
mentioning
confidence: 99%
“…This is suggested by the relationship between the studies of Cook et al (1963) and Corson & Enesco (1966). There are, of course, many other possible causes.…”
Section: Discussionmentioning
confidence: 99%
“…Other stimulants (methylphenidate and methamphetamine) did not have this effect. Cook et al (1963) found that injections of yeast RNA caused rats to learn to pole-climb to avoid shock faster than control animals. However, Corson & Enesco (1966), although able to replicate these results with poleclimbing, were unable to obtain increased learning rates using an escape task which required animals to run down an alley to a goal box.…”
mentioning
confidence: 99%
See 1 more Smart Citation